2020
DOI: 10.1136/thoraxjnl-2020-215768
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection and adverse outcomes in users of ACE inhibitors and angiotensin-receptor blockers: a nationwide case-control and cohort analysis

Abstract: ObjectiveTo examine the impact of ACE inhibitor (ACE-I)/angiotensin receptor blocker (ARB) use on rate of SARS-CoV-2 infection and adverse outcomes.MethodsThis nationwide case-control and cohort study included all individuals in Denmark tested for SARS-CoV-2 RNA with PCR from 27 February 2020 to 26 July 2020. We estimated confounder-adjusted ORs for a positive test among all SARS-CoV-2 tested, and inverse probability of treatment weighted 30-day risk and risk ratios (RRs) of hospitalisation, intensive care uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 33 publications
(38 reference statements)
1
20
0
Order By: Relevance
“…In addition, the epidemiological characteristics of COVID-19 are dynamic and rapidly change within and between countries as the pandemic evolves, and large health care registries may assist in quickly testing scientific hypothesis in different settings. [11][12][13][14][15] However, registrybased analyses using diagnosis codes require that the codes are of high quality and, thus far, the validity of ICD-10 codes for COVID-19 remains unclear. This study aimed to examine the PPV of the ICD-10 diagnosis codes for COVID-19 at departments of infectious diseases in Denmark.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the epidemiological characteristics of COVID-19 are dynamic and rapidly change within and between countries as the pandemic evolves, and large health care registries may assist in quickly testing scientific hypothesis in different settings. [11][12][13][14][15] However, registrybased analyses using diagnosis codes require that the codes are of high quality and, thus far, the validity of ICD-10 codes for COVID-19 remains unclear. This study aimed to examine the PPV of the ICD-10 diagnosis codes for COVID-19 at departments of infectious diseases in Denmark.…”
Section: Introductionmentioning
confidence: 99%
“…Hippisley-Cox et al [20] reported a reduced incidence of COVID-19 infection in those on ACEI/ARB overall but suggested that ARB were signifi- cantly less protective in the Black population than the Caucasian group; ACEI appeared less protective in the Caribbean than the Caucasian group and were associated with an increased risk of COVID-19 disease in the Black population; but neither medication was associated with an increased risk of receiving ICU care in their study. An et al [21] suggested that treatment with ACEI/ARB was not associated with an increased risk for COVID-19 infection, while Morales et al [22] and Christiansen et al [23] discussed that use was neither associated with higher risk nor with any adverse outcomes in patients with CO-VID-19 infection. Lopes et al [24], in their multicenter randomized trial called BRACE CORONA, aimed to evaluate whether discontinuing compared with maintaining chronic ACEI/ARB treatment among hospitalized COVID-19 patients increases days alive and out of the hospital and found no significant differences in outcomes suggesting suspending these medications was not beneficial in anyway.…”
Section: Comparison With Other Studies and Review Of The Literaturementioning
confidence: 99%
“…But, due to the importance of ACEI and ARB in routine clinical practice, articles have been published elaborating on the hypothesis of severe COVID-19 infection in those exposed to these medications [11][12][13][14][15], and several studies have been conducted to assess the true association. None of these have shown an increased risk of mortality or ICU admission in relation to ACEI/ARB [16][17][18][19][20][21][22][23][24][25][26][27][28]. Moreover, some favorable outcomes have been reported in a subset of these studies [20,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, infl ammation of the lung tissue, which is a distinctive characteristic of the disease and determines the originality and severity of its course, is considered as a sign, and not its basis. Various disorders that appear only from the moment of the development of the focus of infl ammation are subjected to attempts to neutralize them as the consequences of infection [43][44][45].…”
mentioning
confidence: 99%